2020
DOI: 10.1111/cpf.12667
|View full text |Cite
|
Sign up to set email alerts
|

Increased arterial stiffness in males with abdominal aortic aneurysm

Abstract: Background Abdominal aortic aneurysm (AAA), a localized dilatation of the abdominal aorta, has a prevalence of about 1.5%–3% among 65‐ to 70‐year‐old males in Europe. AAA confers an increased risk of developing major cardiovascular events in addition to the risk of aneurysm rupture. The aim of this study was to evaluate whether the arterial wall distensibility is altered in subjects with AAA. Methods Two hundred and eighty‐four male subjects (182 with AAA and 102 controls) were enrolled in the study. Arterial … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
14
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 16 publications
(17 citation statements)
references
References 39 publications
(41 reference statements)
0
14
0
Order By: Relevance
“…It is widely recognized that AAA disease is associated with cardiovascular events not directly related to the aneurysm, but the extent to which AAA is associated with general aortic disease is less clear [ 6 ]. Åström Malm et al [ 11 ] recently reported increased aortic stiffness in males with AAA compared to matched controls based on the carotid-to-femoral pulse wave velocity (PWV) method. Further studies with 4D Flow CMR-based regional PWV estimation may establish whether increased stiffness in AAA patients occurs uniformly throughout the aorta or mainly in the infrarenal abdominal aorta.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It is widely recognized that AAA disease is associated with cardiovascular events not directly related to the aneurysm, but the extent to which AAA is associated with general aortic disease is less clear [ 6 ]. Åström Malm et al [ 11 ] recently reported increased aortic stiffness in males with AAA compared to matched controls based on the carotid-to-femoral pulse wave velocity (PWV) method. Further studies with 4D Flow CMR-based regional PWV estimation may establish whether increased stiffness in AAA patients occurs uniformly throughout the aorta or mainly in the infrarenal abdominal aorta.…”
Section: Discussionmentioning
confidence: 99%
“…For example, the co-prevalence of AAA and thoracic aortic aneurysm is 10–30% [ 7 9 ]. Further, recent studies associated AAA with increased left-ventricular workload and faster ageing of the central arteries [ 10 , 11 ].…”
Section: Introductionmentioning
confidence: 99%
“…AAA <55 mm is classified as a small AAA. The controls had an absolute infrarenal aortic diameter within the reference range (<30 mm), and no sign of ectasia, at their screening examinations during the past 5 years (Åström Malm et al, 2020).…”
Section: |mentioning
confidence: 99%
“…Increased arterial stiffness as well as generalized arteriomegaly have been demonstrated in AAA patients (Åström Malm et al, 2020;Johnsen et al, 2009). This indicates that AAA may be a systemic disease rather than a local disease, and moreover that its pathological process is not confined to the abdominal aorta.…”
mentioning
confidence: 97%
See 1 more Smart Citation